Prevalence of thumb sucking in children and its effect on dentoalveolar abnormality, Babol, 2001 - M Ghasem Pour (Babol University of Medical Sciences, 2003)
Background and Objective: The prevalence of thumb sucking is different in various societies according to their socio-economic condition. The objective of this study was to evaluate the prevalence of this habit and its effect on dentoalveolar abnormality in Babol. Methods: This study was performed on 374 children aged 5-6 years old in public and private kindergarten in Babol. Data was gathered by 2 questionnaires and then they were statistically analyzed by Chi-square test. Findings: Among 374 children, 20.1% had thumb sucking and there was not any significant relationship between boys and girls. Also, overjet (74.7%), open bite (48%), cross bite (54.7%), tongue thrust (56%), and deep and narrow palate (42.7%) were more prevalent in thumb sucker group. Conclusion: With regard to high prevalence of thumb sucking in this community and results of this habit, it seems that giving more information to parents about etiologic factors, how to quit this habit and early treatment can be effective for prevention and limitation of other abnormalities.